2005
DOI: 10.1093/bja/aeh289
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious auditory priming during surgery with propofol and nitrous oxide anaesthesia: a replication

Abstract: Existing knowledge can be primed by information presented during propofol and nitrous oxide anaesthesia. This priming is evidence of unconscious information processing and not the result of moments of awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 15 publications
4
28
2
2
Order By: Relevance
“…Hormonal stress responses may increase the chance of priming during surgery compared with before surgery, but two studies using BIS to control anesthetic depth during surgery found no evidence of priming using the Robinson Crusoe story (Struys et al, 1998) and a category generation task . However, with a word stem completion test, we demonstrated priming during surgery with an anesthetic that was relatively deep on average (Deeprose et al, 2004) and replicated that finding in patients for whom anesthetic depth remained below a BIS value of 60 throughout word presentation (Deeprose et al, 2005). The difference between our results and those of and Struys et al (1998) may reflect our use of a perceptual rather than conceptual priming task.…”
Section: Eeg-bispectral Indexsupporting
confidence: 78%
See 3 more Smart Citations
“…Hormonal stress responses may increase the chance of priming during surgery compared with before surgery, but two studies using BIS to control anesthetic depth during surgery found no evidence of priming using the Robinson Crusoe story (Struys et al, 1998) and a category generation task . However, with a word stem completion test, we demonstrated priming during surgery with an anesthetic that was relatively deep on average (Deeprose et al, 2004) and replicated that finding in patients for whom anesthetic depth remained below a BIS value of 60 throughout word presentation (Deeprose et al, 2005). The difference between our results and those of and Struys et al (1998) may reflect our use of a perceptual rather than conceptual priming task.…”
Section: Eeg-bispectral Indexsupporting
confidence: 78%
“…In a second study, we replicated the finding of priming during surgery using the same stimuli and tests as before, and provided stronger evidence that priming occurs in the absence of awareness (Deeprose, Andrade, Harrison, & Edwards, 2005). Each stimulus word was presented 15 times and BIS was recorded at the start and end of each series of repetitions.…”
Section: Eeg-bispectral Indexsupporting
confidence: 59%
See 2 more Smart Citations
“…83,84,86 Evidence suggests that implicit memory priming can be facilitated by surgical stimulation under anesthesia. 87,88 In part, this seems plausible because cortisol is released into circulating blood as a response to surgical stress, which then activates the amygdala. 89 Involvement by this part of the limbic system is responsible for emotional memory.…”
Section: Priming and Anesthesiamentioning
confidence: 99%